Realizing the Trifunctional Potential of Alkyl 4-Chloro-2-diazo-3-oxobutanoates: Convenient Assembly of 6,7-Dihydro-4H-[1,2,3]triazolo[5,1-c][1,4]thiazine Core - Dar’in, Dmitry; Khoroshilova, Olesya; Kantin, Grigory; Krasavin, Mikhail (Synthesis, 2020)
The first example of exploiting the trifunctional character of alkyl 4-chloro-2-diazo-3-oxobutanoates in the reactions with vicinal N,S-bis-nucleophiles leading to the formation of bicyclic 6,7-dihydro-4H-[1,2,3]triazolo[5,1-c][1,4]thiazines is presented. The key to the successful realization of the atom-economical synthetic strategy is the initial SN2 event, which facilitates the subsequent domino 1,2,3-triazole formation via the Wolff reaction. Equally important is the choice of sodium acetate as the base: acetic acid formed in the course of the initial nucleophilic substitution acts as an efficient catalyst for the Wolff reaction, which suppresses the competing, unwanted fragmentation path (observed when other bases are used).
Keywords: diazo transfer; multicenter reactions; nucleophilic substitution; domino reactions; Wolff 1,2,3-triazole synthesis